Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 7115 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Bivalvia", "Geometry POLYGON((-126 42,-126 32,-114 32,-114 42,-126 42))", "HasGeospatialIssue is false", "BasisOfRecord is Specimen", "StateProvince is California" ] } The dataset includes 7115 records from 15 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0021097-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences